2018
DOI: 10.1371/journal.pone.0192867
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency classification of children with autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a wide-ranging collection of developmental diseases with varying symptoms and degrees of disability. Currently, ASD is diagnosed mainly with psychometric tools, often unable to provide an early and reliable diagnosis. Recently, biochemical methods are being explored as a means to meet the latter need. For example, an increased predisposition to ASD has been associated with abnormalities of metabolites in folate-dependent one carbon metabolism (FOCM) and transsulfuration (TS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The FDA‐sub model had the best validation performance with a false positive rate of 19/154 at an expected false negative rate of 5%. As expected, these misclassification rates are higher than the false negative rate of 3.6% at a false positive rate of 2.6% found previously due in part to the absence of “% DNA methylation” and “8‐OHG” in the validation data, two of the most important variables for separating ASD and TD cohorts . CART and LR of a subset of metabolites produced results that were slightly worse than PCA with false positive rates of 38/154 and 32/154, respectively; both of these results are at an expected false negative rate of 5%.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…The FDA‐sub model had the best validation performance with a false positive rate of 19/154 at an expected false negative rate of 5%. As expected, these misclassification rates are higher than the false negative rate of 3.6% at a false positive rate of 2.6% found previously due in part to the absence of “% DNA methylation” and “8‐OHG” in the validation data, two of the most important variables for separating ASD and TD cohorts . CART and LR of a subset of metabolites produced results that were slightly worse than PCA with false positive rates of 38/154 and 32/154, respectively; both of these results are at an expected false negative rate of 5%.…”
Section: Discussionsupporting
confidence: 46%
“… Including the same variables in the training and validation data. Previous analyses found that “% DNA methylation” and “8‐OHG” were two of the most important variables for separation, but these data were not present in the validation set. Future studies should include these variables to allow for the highest possible classification accuracy as these classifiers are considered for clinical translation into a diagnostic test. Including both ASD and TD populations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations